De dødes landskap: Måtte man begraves ved sognekirken i middelalderen? - Brendalsmo, A. Jan (Hikuin, 2000)
The landscape of the dead. Was burial at the parish churchyard an obligation in the Middle Ages? By A. Jan Brendalsmo Too often one finds that scientists doing research on the skeletal material found in parish churchyards draw firm conclusions about the people who once inhabited the adjoining areas. This probably arises from the assumption that it was obligatory in the Middle Ages, after the establishment of geographically delimited parishes, for people to receive burial at the local parish church. However, analyses of contemporary written sources concerning the see of Nidaros in Northern Norway shows that this cannot have been the case. The only thing that can be stated with certainty is that all law-abiding Christian members of society were to receive burial at a church, while those who had committed certain severe crimes were to be buried “where sea meets land”. Furthermore, it seems that common and more or less private cemeteries coexisted in the area throughout the Middle Ages, and that the location of a particular individual’s grave depended to a large extent on the social and economic standing of the deceased, rather than on his or her place of domicile. As a result, the author argues that – in addition to the familiar (and later) geographical parish – there were two other kinds of parish in the Middle Ages: the “social parish” and the “religious parish”. The main conclusion is thus that the “landscape of the dead” reflects the complexity of the world of the living, and that it is not possible, a priori, to regard the physical remains found in a local churchyard as directly representative of the area’s contemporary population.